Comparison of usability of text editors MS Word 2003, MS Word 2007 and OpenOffice Writer 3.0 - Andziulienė, Beatričė; Jucys, Žilvinas (Lietuvos matematikos rinkinys, 2009)
In order to address ergonomic problems in the process of education, education relevant to the use of ergonomic work tools. The article includes educational process is widely used in a text editor usabilityresults of the study, of the performance experiment. Operating results of the experiment showed that MS Office Word 2007 usability respect ahead of MS Word 2003 and OpenOffice Writer 3.0 applications: task completion time for work in MS Word 2007 editor is 5 percent lower than the same task in MS Word 2003 and 8 percent lower then in Open Office Writer 3.0 editor; navigational errors in learning a task using MS Word 2007 and Word 2003 decreased by 9 times on average, while using OpenOffice Writer 3.0 approximately 3.5-times; task performance accuracy (formatting error) is the best on MS Word 2007, there’s no errors then task is learned. The fact that OpenOffice Writer is a free open source product, this is a relatively well-developed alternative to the commercial Microsoft Office Word.
Keywords: usability evaluation; text editor; performance experiment; educational process